FIZIKA FANIDAN LABORATORIYA MASHG‘ULOTLARIDA TAJRIBA NATIJALARINI QAYTA ISHLASH METODIKASI - Kanatbayev, S.S. (SCIENCE and SOCIETY, 2024)
The article analyzes the essence and structure of a physical experiment, as well as the importance of taking into account measurement errors processing and identifying the results of physical experiments in laboratory physics classes.